2016
DOI: 10.3390/su8040374
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Water Resources in Horqin Sandy Land Using Multisource Data from 2003 to 2010

Abstract: Over the past four decades, land use/land cover (LU/LC) change, coupled with persistent drought, has resulted in the decline of groundwater levels in Horqin Sandy Land. Accordingly, this study quantifies changes in LU/LC and groundwater storage (GWS). Furthermore, it investigates the effects of LU/LC changes on GWS. GWS changes are estimated using Gravity Recovery and Climate Experiment (GRACE) data and ground-based measurements obtained from July 2003 to December 2010. Soil moisture and snow water equivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
4
1
Order By: Relevance
“…GWS depletion rate in the WLRB from these annual well observations is −0. A recent study by Zhao et al [36] only used groundwater level data from the CIGEM to estimate GWS changes in the WLRB plain and found a rate of −2.76 ± 0.15 cm/yr from 2005 to 2009, which significantly overestimated the actual GWS depletion rate when compared to results from our study and the aforementioned previous studies. As shown in Figure S4, the distribution of groundwater wells from the HBIM is relatively uniform; while the monitoring wells from the CIGEM are mainly located in the two cones of groundwater depression centered within the WLRB, explaining the likely overestimation of GWS depletion.…”
Section: Comparison With Other Studiescontrasting
confidence: 86%
See 1 more Smart Citation
“…GWS depletion rate in the WLRB from these annual well observations is −0. A recent study by Zhao et al [36] only used groundwater level data from the CIGEM to estimate GWS changes in the WLRB plain and found a rate of −2.76 ± 0.15 cm/yr from 2005 to 2009, which significantly overestimated the actual GWS depletion rate when compared to results from our study and the aforementioned previous studies. As shown in Figure S4, the distribution of groundwater wells from the HBIM is relatively uniform; while the monitoring wells from the CIGEM are mainly located in the two cones of groundwater depression centered within the WLRB, explaining the likely overestimation of GWS depletion.…”
Section: Comparison With Other Studiescontrasting
confidence: 86%
“…Thus, it is crucial to evaluate the state of groundwater resources in the WLRB for the development of sustainable agriculture and the preservation of terrestrial ecosystems. Groundwater level declines in the WLRB within the past two decades have been reported by several studies [33][34][35][36], e.g., with a rate of ~−0.18 m/yr from 1999 to 2010 [29]. Average groundwater levels in three main counties of the WLRB in 2006 decreased by 3.8 m, 2.8 m, and 1.9 m, respectively, when The WLRB is located in a semi-arid region, with an area of 136,000 km 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Long-term dry conditions and extensive groundwater mining for agricultural, industrial and domestic consumption result in significant groundwater declines in the LRB in the past two decades [94]. Based on GRACE data, Zhao et al [95] found a GWS decline rate of 13.5 ± 1.9 mm/yr from 2003 to 2010 and the largest GWS depletion rate of 26 mm/yr for 2005-2009 in Horqin Sandy Land, i.e., the upstream of the Liaohe River including Tongliao City, which is consistent with limited six monitoring well observations they collected from the CIGEM. Zhong et al [46] found a GWS decline rate of 6.8 ± 3.6 mm/yr during 2005-2011 in the western LRB using GRACE.…”
Section: Song-liao Basinmentioning
confidence: 99%
“…However, previous findings showed that water addition has an effect on plant functional traits in a typical steppe [10], and plant height was low in dry conditions [41]. It is probably attributed to plants having been acclimated themselves to the local environment in Horqin sandy grassland, further suggesting that water addition is not a proper way to maintain the sustainable development of sandy grassland in Horqin because of the decline of groundwater caused by unreasonable irrigation and climate change in Horqin sandy land [22,42]. Moreover, water addition reduced plant height in fencing and N addition treatments in our study, indicating that water addition interacted with fencing, and N supply is not favor plant growth in the sandy grassland.…”
Section: Discussionmentioning
confidence: 99%